Measuring Money Attitudes and Beliefs - Adrian Furnham (Encyclopedia, 2025)
Over the last 50 years, there have been many attempts to devise and validate questionnaires to assess an individual’s attitude toward money and related issues. This paper attempts to conduct a comprehensive review of those measures. In all, this paper documents 54 salient studies and consults many other references from diverse and multi-disciplinary literature. There is evidently a great deal of overlap in the money attitudes dimensions assessed. Research has concentrated on the correlates of these attitudes (cultural, demographic, financial, and personality). Suggestions for the choice and development of measures are made, along with propositions for future research.